Fluid Inclusion, Isotopic, and Elemental Geochemistry Studies of Cave-Filling Calcite in the Lower–Middle Ordovician Yingshan Formation of Tahe Oilfield, NW China: Implication for Karstification in Non-exposed Limestone - Zhang, Yongmei; Zhang, Shaonan; Huang, Baiwen; Lu, Ziye; Ye, Ning; Zhu, Bei; Hou, Xianhai; Xie, Fei; Bai, Xiaoliang; Zhang, Xinyan (Frontiers in Earth Science, 2022)
Improving the recognition of paleo-fluid circulation history is of great significance to reconstruct pore evolution during carbonate diagenesis. Integrated petrography, fluid inclusion, isotopic and elemental geochemistry (LA-ICP-MS) studies, calcites generated in paleo-caves, and fractures were investigated. This study aims to reveal the paleo-fluid origin and karstification event within the non-exposed limestone of the Lower-Middle Ordovician Yingshan Formation in the Tarim Basin. The only generation of blocky calcite growing along the karst paleo-cave and fracture walls (CFC), crosscuts burial stylolites. The secondary fluid inclusions obtained from CFC are characterized by the coexistence of liquid-only and liquid-dominated aqueous inclusions with low salinities values (0–2.4 wt%), suggesting that the CFC has experienced a low-temperature environment (<50 °C). The depleted δ18O values (-15.32–-12.45 ‰), seawater-like REEY patterns, and low ΣREE (<0.65 ppm) have recorded the major episode of meteoric water leaching the Yingshan limestone. This view was further confirmed by the calculated δ18Owater values of parent fluids (-14.3–-2.2‰). The relatively higher 87Sr/86Sr ratios (0.70942–0.70994) are interpreted as the result of meteoric water interacting with the overlying Silurian detrital rock when percolated downward. The geochemical evidence recorded by CFC indicates that the karstification event for Yingshan non-exposed limestone possibly took place in the Early Hercynian period during the late Devonian. Therefore, meteoric water percolating downward along the fractures penetrating insoluble strata and/or migrating laterally along the permeable strata, are deemed responsible for the karstification event although the overlying thick insoluble strata in the coverage area.